2022
DOI: 10.3390/jcdd9040095
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Discharge Mode on the Distribution of Myocardial Pulsed Electric Field—A Simulation Study for Pulsed Field Ablation of Atrial Fibrillation

Abstract: Background: At present, the effects of discharge modes of multielectrode catheters on the distribution of pulsed electric fields have not been completely clarified. Therefore, the control of the distribution of the pulsed electric field by selecting the discharge mode remains one of the key technical problems to be solved. Methods: We constructed a model including myocardium, blood, and a flower catheter. Subsequently, by setting different positive and ground electrodes, we simulated the electric field distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In the computational studies of PFA in AF treatment, to shorten the model construction process and reduce the computational complexity, the LA model is usually defined as a regular shape model such as a sphere [ 39 ] or a cylinder [ 41 ], and the fiber orientation is ignored; or the LA model is based on 3D medical imaging reconstruction [ 3 , 4 ] and the fiber orientation is ignored. Although Xie et al [ 1 ] constructed a myocardial model composed of multi-layer circular slabs and simulated fiber orientation by assigning an AC tensor to each layer, such regular fiber orientation still cannot reflect the influence of realistic fiber orientation on ablation characteristics in PFA in AF treatment consistently.…”
Section: Discussionmentioning
confidence: 99%
“…In the computational studies of PFA in AF treatment, to shorten the model construction process and reduce the computational complexity, the LA model is usually defined as a regular shape model such as a sphere [ 39 ] or a cylinder [ 41 ], and the fiber orientation is ignored; or the LA model is based on 3D medical imaging reconstruction [ 3 , 4 ] and the fiber orientation is ignored. Although Xie et al [ 1 ] constructed a myocardial model composed of multi-layer circular slabs and simulated fiber orientation by assigning an AC tensor to each layer, such regular fiber orientation still cannot reflect the influence of realistic fiber orientation on ablation characteristics in PFA in AF treatment consistently.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, one recent study found that the discharge mode also affects the PEF in the myocardium. 31 Catheter shape is another important factor. PEF system can be applied through many different catheter types, such as needle, 32,33 linear, 34 balloon, 35 basket, [36][37][38][39][40] lattice, 41 and circular [42][43][44] catheters (Table 1).…”
Section: Parameters Of Pef Deliverymentioning
confidence: 99%
“…Moreover, one recent study found that the discharge mode also affects the PEF in the myocardium 31 . By setting different positive and ground electrodes, Ji et al.…”
Section: Parameters Of Pef Deliverymentioning
confidence: 99%
“…However, this computational model did not include the detailed geometric structure of the heart (epicardial fat, GPs, myocardium and blood), nor the effect of the saline infusion. To date, computer modelling has been mainly used to study endocardial PFA (i.e., where the ablation electrodes are immersed in the cardiac chamber, surrounded by blood and placed on the endocardium solely on the area to be ablated) [ 6 , 7 , 8 ]. Relevantly, the study by Verma et al [ 6 ] suggested that the presence of tissues with very different electrical conductivity caused large electric field gradients.…”
Section: Introductionmentioning
confidence: 99%